An analysis of the interdependence within the bilateral relationship between South Africa and Lesotho - Grimwood, Zahira (Department of Political Studies, 2017)
The main objective of this minor dissertation is to unpack the convoluted bilateral relationship between the Kingdom of Lesotho and the Republic of South Africa. Lesotho's extreme dependence on South Africa is explored in terms of geopolitical dependence, labour migration, the Southern African Customs Union (SACU) and royalties accrued from the Lesotho Highlands Water Project (LHWP). The exhaustive amount of literature that explores these themes of Lesotho's dependence clearly reflects the dominance of South Africa during the apartheid and post-apartheid eras. A factor that further complicates these analyses is that South Africa, an 'economic giant' on the African continent, is dependent on the water resources of the politically and economically weaker, landlocked Lesotho. In consideration of South Africa's dependence on Lesotho's water, the relationship can be regarded as an interdependent relationship. The concept of interdependence and the theory of complex interdependence provide some theoretical basis from which to analyse the 'web of interactions' between the two countries. While apartheid South Africa was regarded as the quintessential realist actor, the post-apartheid government aimed to shed the skin of its predecessor's hegemonic pursuits in southern Africa. Post-apartheid South Africa has faced criticism as a nation-state that has unilaterally manipulated Lesotho in pursuit of maintaining its national interest, reducing the values of transfers from dependence factors. While the relationship may be characterised as asymmetrical interdependence, the nature of the relationship is not entirely the same as in the post-apartheid era. Each factor of dependence needs to be reflected on in order to shed light on the historical and current contexts that shows that the likelihood of interdependence would be sustained. South Africa's role should not be perceived merely in terms of power manipulation, but also in terms of factors of benevolence and cooperation that have changed the nature of the relationship between the two countries. In addition, there are factors not determined by South Africa that help to maintain the politically and economically fragile position of Lesotho.